Історично-археологічні дослідження післямонгольських та козацьких часів в Україні - Моця, О.П. (Археологія, 2016)
На історичному проміжку часу між навалою орд Батия і припиненням функціонування Української козацької держави на півдні Східної Європи відбувались досить важливі процеси, зокрема формування нового етносу. Археологічні джерела для їх висвітлення досі використовуються недостатньо. Study of the 14th—17th century sites remains to be a problem issue in home archaeology; the fact that it’s underdeveloped is explained by a series of objective and subjective reasons of the Soviet past, including the «Ukrainian bourgeois nationalism struggle», and by the scholars’ disinterestin the study of «non-archaeological period». Therefore,the historians-mediaevalists studying the written sources reached the higher qualitative standard in their developments, in comparison with the archaeologists. Nevertheless, various archaeological material is already accumulated today, and still is being accumulated; it is referred to the post-Mongols and the Cossacks times and should be comprehensively analyzed and certainly be presented in form of archaeological map. Solving of this matter in future will allow developing into other urgent issues in studying the process of development of Ukrainian nation’s material culture in the Late Mediaeval and the Early Modern Periods. Изучение памятников ХІV—ХVІІ вв. остается проблемной темой отечественной археологии, недостаточная разработка которой объясняется рядом объективных и субъективных причин советского прошлого (в том числе и «борьбой с украинским буржуазным национализмом») и незаинтересованностью специалистов в изучении «неархеологического периода». Поэтому историки-медиевисты, изучающие письменные источники, в этом отношении вышли на более качественный уровень в своих разработках по сравнению с археологами. И все же нынче уже накоплен (и далее продолжает увеличиваться) разнообразный археологический материал, относящийся к послемонгольскому и казаческому времени, который необходимо комплексно проанализировать и, обязательно, представить в виде археологической карты. Решение этого вопроса позволит в дальнейшем перейти к рассмотрению многих других актуальных тем, в изучении процесса развития материальной культуры украинского народа во времена позднего средневековья и раннего модерна.